The Role of Female Pembarong and Humanistic Values in the Barongan Samin Edan Performance in Semarang (Universitas Negeri Semarang, 2022)
Barongan dancers (Pembarong) are selected based on the level of the individual's movement technique ability and their popularity as pembarong (Slamet, 2003, p. 27). Pembarong is generally performed by men considering the size of the mask and the character that must be performed, which depicts tigers with strong, ferocious, savage, agile, and mighty characters. Therefore, it has a small chance to be performed by women. However, there is something different about the Samin Edan Semarang barongan performance, which shows female pembarong. The performance is packaged in such a way so that it raises various questions about the role of female pembarong based on gender requirements. Accordingly, the researchers are interested in examining these problems related to humanistic values in the Samin Edan Semarang barongan performance. This research used an interdisciplinary approach. Two data collection steps were used in this study, namely the field and the literature data collection. The field data was conducted through observation, interviews, and document studies. Data analysis techniques in this study used interactive data analysis, according to Miles and Huberman to analyze the position and role of female pembarong in the Samin Edan Group Barongan performance in Semarang and the humanistic values reflected in it. The study's results show the role of women and humanistic values in the Samin Edan Barongan performance. In conclusion, the open opportunities for women in the creative process in the Samin Edan Barongan performance show that there are no restrictions on social territory structurally, nor are there any attempts to differentiate the roles of men and women through different dance types, forms, material, or structure. Humanistic values are reflected in the creative process of Barongan Samin Edan. The implication gives space for free expression to all dancers to be the key to the creative process of Barongan Samin Edan. It is because the dance manifests the choreographer's hopes always to offer a liberating artistic experience. It is important to reposition the creative process that forms an individual's humanist character and the idea that education through art is actually the basis for the formation of a humanist character.